ANALISIS PUTUSAN PENGADILAN NEGERI JAMBI NOMOR 516/PID.B/2019/PN.JMB DITINJAU DARI PRINSIP ULTRA PETITA - Defarai Qarima Darmawan; Hery Firmansyah (Fakultas Hukum Universitas Tarumanagara, 2022)
The judge in deciding a criminal case must be based on the indictment of the public prosecutorand everything that is proven at trial. The problem faced in the research is how the ultra petitalimit in imposing criminal sanctions by judges and how the Jambi District Court Decision No.516/Pid.B/2019/PN.Jmb analyzes the ultra petita theory. The research method used is normativejuridical law research. The results of the study indicate that the ultra petita limit in imposingcriminal sanctions by judges is that it must not exceed the maximum threat of the article charged,it is not allowed to give a criminal decision whose type of crime has no reference in the CriminalCode, or criminal regulations outside the Criminal Code and the sentencing decision must giveconsideration suf iciently evidence-based. Jambi District Court Judge Number516/Pid.B/2019/PN.Jmb has given an ultra petita decision, in which case the Public Prosecutor inhis indictment demands a sentence of 10 years in prison for the defendant with a reduction whilethe defendant is in prison. in detention based on his order that the accused remain in detention.However, the Panel of Judges tried and sentenced the defendant for 12 years. In this case, thejudge has decided on the case and sentenced him to imprisonment in accordance with themaximum penalty in the Criminal Code. There must be a normative regulation regarding theexistence of ultra petita decisions that may be made by judges.